Effectiveness of biomedical interventions on the chronic stage of traumatic brain injury: a systematic review of randomized controlled trials - Kawata, Keisuke; Rettke, Devin J.; Thompson, Christopher; Mannix, Rebekah; Bazarian, Jeffrey J.; Datta, Dibyadyuti (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI), in any form and severity, can pose risks for developing chronic symptoms that can profoundly hinder patients’ work/academic, social, and personal lives. In the past 3 decades, a multitude of pharmacological, stimulation, and exercise-based interventions have been proposed to ameliorate symptoms, memory impairment, mental fatigue, and/or sleep disturbances. However, most research is preliminary, thus limited influence on clinical practice. This review aims to systematically appraise the evidence derived from randomized controlled trials (RCT) regarding the effectiveness of pharmacological, stimulation, and exercise-based interventions in treating chronic symptoms due to TBI. Our search results indicate that despite the largest volume of literature, pharmacological interventions, especially using neurostimulant medications to treat physical, cognitive, and mental fatigue, as well as daytime sleepiness, have yielded inconsistent results, such that some studies found improvements in fatigue (e.g., Modafinil, Armodafinil) while others failed to yield the improvements after the intervention. Conversely, brain stimulation techniques (e.g., transcranial magnetic stimulation, blue light therapy) and exercise interventions were effective in ameliorating mental health symptoms and cognition. However, given that most RCTs are equipped with small sample sizes, more high-quality, larger-scale RCTs is needed.